KEBIJAKAN PENGEMBANGAN OBJEK WISATA PEMANDIAN LUBUK TAMPURUNG DIKELURAHAN KURANJI KECAMATAN KURANJI KOTA PADANG PROVINSI SUMATERA BARAT - Helmawati Helmawati (Jurnal Apresiasi Ekonomi, 2017)
The only tourism attraction with waterfall based located closest to the center of Padang city administration.isPemandianLubukTampuruang. This attraction is still natural, had not been built and managed by local government as well as the private sector in the Belimbing sub district, The district of Belimbing, Padang,West Sumatra province. Therefore, the purpose of this study is to formulate appropriate policies to be applied in the development of tourism attractions that can improve Micro, Small, Medium EnterpriseS (UMKM) in the area. This research employed SWOT analysis, by analyzing the strengths and weaknesses (internal), opportunities and threats (external) in the tourism object Pemandian LubukTampuruang. The data used are primary data and secondary data. Based on this research, its main strength is that it is the only waterfall tourist attraction in the city that is easy to be reached, while the weakness is inadequate infrastructure.The opportunitiesof this attraction is it has the potential to be a good quality tourism attraction while the threats to be anticipated is a sudden natural disaster that would have a negative impact and impede the development of the attraction. Suggested strategy in developing Pemandian LubukTampuruang Baths is SO strategy (Strengths Opportunitis) which is a strategy to maximize the existing strengths in the location to seize opportunities that will make this attraction even better than before.